THE ROLE MEDIATION INNOVATION-BASED PUBLIC SERVICES: ORGANIZATIONAL CULTURE TOWARD EMPLOYEE PERFORMANCE: THE ROLE MEDIATION INNOVATION-BASED PUBLIC SERVICES: ORGANIZATIONAL CULTURE TOWARD EMPLOYEE PERFORMANCE - Putri, Zhelika Nurul; Seswandi, Agus; Supeno, Bambang (PENANOMICS: International Journal of Economics, 2025)
Organizational culture plays a very important role in shaping the identity and excellence of anorganization, both in the public and private sectors. An organizational culture that supportsopenness, collaboration, and risk-taking can accelerate the innovation process and enableorganizations to be more adaptive to change and create new products and services that meet theneeds of society; a strong culture that is aligned with organizational strategy can improve employeeperformance. This study aims to examine the mediating role of innovation-based public services:organizational culture and employee performance of the Siak Regency Regional Secretariat. Thisstudy uses a quantitative method by distributing questionnaires via Google Forms to 100 people.Data is processed using SmartPLS 3.2.9 software. The data analysis method uses structural equationmodeling-partial least square (SEM-PLS). The results of the study indicate that organizationalculture has a positive and significant effect on innovation-based public services, and innovationbased public services has a positive and significant effect on employee performance. Organizationalculture has a positive and significant effect on employee performance. Innovation-based publicservices is able to mediate the influence between organizational culture and employee performance.In conclusion, the influence between organizational culture, innovation-based public services, andemployee performance is still growing. By understanding the mechanisms underlying thisrelationship, the Siak Regency Regional Secretariat can design more effective service programs toimprove employee innovation and performance